3D Multi‐Copter Navigation and Mapping Using GPS, Inertial, and LiDAR. Issue 2 (1st June 2016) - Dill, Evan T.; Uijt de Haag, Maarten
Abstract: As the use of unmanned aerial vehicles has become more prevalent, the need for a reliable three‐dimensional positioning and navigation capability is required to enable operation in challenging environments where the Global Positioning System (GPS) may not be available. For many of these environments, there may not be one particular method to solve the positioning navigation problem. Therefore, we have selected a set of dissimilar sensor technologies and implemented an integrated navigation method that can support reliable operation in an outdoor and structured indoor environment. The integrated navigation design is based on three types of sensors: a GPS receiver, an inertial measurement unit, and three laser scanners. This paper will show that decimeter‐level relative positioning accuracies can be achieved for structured indoor operations and that when segments are included where GPS is available, the platform's trajectory is globally anchored with meter‐level accuracy. A secondary goal of the proposed method is the generation of a three‐dimensional map of the environment. Copyright © 2016 Institute of Navigation Copyright © 2016 Institute of Navigation